2006
DOI: 10.1128/cvi.00076-06
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Monocytes in Stimulating Human Peripheral Blood Mononuclear Cells with Lactobacillus casei To Produce Cytokines and Augment Natural Killer Cell Activity

Abstract: We examined the effect of a probiotic strain, Lactobacillus casei strain Shirota, on cytokine production and natural killer (NK) cell activity in human peripheral blood mononuclear cells (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 40 publications
11
68
1
Order By: Relevance
“…Our data is consistent with previous studies showing that probiotic bacteria are able to induce TNF-α secretion in human PBMC [8,10,11,17] . However, there were considerable differences in the ability of different probiotic bacteria to induce IL-12 and IFN-γ.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data is consistent with previous studies showing that probiotic bacteria are able to induce TNF-α secretion in human PBMC [8,10,11,17] . However, there were considerable differences in the ability of different probiotic bacteria to induce IL-12 and IFN-γ.…”
Section: Discussionsupporting
confidence: 83%
“…In human PBMCs gram-positive bacteria induce TNF-α [8][9][10] , IL-12 [11][12][13][14][15] and IFN-γ [10,11,13,15] while gramnegative bacteria have preferentially been suggested to induce IL-10 production [14] . Gram-positive bacteria or their structural components activate cells via TLR2, whereas gram-negative bacteria and their major structural component lipopolysaccharide activate host cell via TLR4 [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, live Lactobacillus casei Shirota (LcS) was able to enhance NK activity in PBMCs [31]. Besides, heat-killed LcS stimulated IL-10, IL-12 and TNF-α and promoted NK cells activity [32]. In our model, combinations of LcV+PppA, LcM+PppA, LcV and LcM increased IL-2 induction; thus, this fact, together with IL-10 increase, would be involved in NK stimulation.…”
Section: Discussionmentioning
confidence: 74%
“…Nevertheless, there is growing evidence that probiotics have immunomodulatory properties and that these properties of probiotics are strain-dependent (32)(33)(34)(35)(36)(37)(38)(39)(40)(41) . For example, there is consistent evidence that a number of probiotics enhance natural killer (NK) cell activity in vitro (40)(41)(42)(43) and there is some supportive evidence that this also occurs in vivo (44)(45)(46) . Probiotic strains whose cell walls are resistant to digestion appear to be particularly potent enhancers of NK activity; it is suggested that monocytes phagocytose the probiotic bacteria and the insoluble cell wall components induce the production of IL-12, which augments NK cell activity (38,47) .…”
Section: Probiotics Ageing and Immunitymentioning
confidence: 99%